Fe-Zn double-metal cyanide complexes as novel, solid transesteritication catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Journal of Catalysis, 2006)
Fe-Zn double-metal cyanide complexes are currently used as catalysts for the ring-opening polymerization of epoxides, as well as the coupling of epoxides and CO2 for the production of polycarbonates. We report their novel application as highly efficient solid catalysts for the transesterification reactions of carbonates. The catalysts were prepared from aqueous solutions of ZnCl2 and K4Fe(CN)(6) in the presence of tert-butanol (complexing agent) and tri-block copolymer EO20PO70EO20 (average molecular weight, 5800; co-complexing agent). They were characterized by chemical analysis, XRD, thermal analysis, N-2 adsorption, magnetic susceptibility, SEM, and FTIR, diffuse reflectance UV-visible, EPR, and X-ray photoelectron spectroscopies. Their acidity was determined from the IR spectra of adsorbed pyridine and the temperature-programmed desorption of NH3. Catalyst samples prepared with both complexing and co-complexing agents were found to be more acidic and catalytically active than those prepared without these agents. These catalysts are more active/selective than other solid catalysts hitherto reported. Dimethyl carbonate, for example, could be synthesized with 100% selectivity and an isolated yield of >86% by the reaction of propene carbonate with methanol. The catalysts can be recycled without significant loss in activity. Lewis acidic Zn ions are the possible active sites for the transesterification reaction. (c) 2006 Published by Elsevier Inc.
Keywords: cyclic carbonate; Dimethyl carbonate; double metal cyanide Fe-Zn complexes; organic carbonate; transesterification catalyst

Hydrophobic, solid acid catalysts for production of biofuels and lubricants - Sreeprasanth, Pulinthanathu Sree; Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2006)
A novel application of Fe-Zn double-metal cyanide (DMC) complexes as solid catalysts in the preparation of fatty acid alkyl esters (biodiesel/biolubricants) from vegetable oils is reported. The catalysts are hydrophobic (no H2O adsorption at reaction temperatures) and contain only Lewis acidic sites (NH3 and pyridine adsorption). Bronsted acid sites are absent (absence of 1546 and 1639 cm(-1) bands on adsorption of pyridine). Basic sites are also absent (no CO2 adsorption). Unlike the homogeneous or other solid catalysts (like ZnO-Al2O3, for example), the Fe-Zn, DMC catalysts are highly active even for the simultaneous transesterification of triglycerides and esterification of the free fatty acids (FFA) present in unrefined and waste cooking oils as well as non-edible oils. They are also tolerant of water, probably, due to their surface hydrophobicity. A relationship between the transesterification activity and the concentration of strong Lewis acid sites has been observed. Coordinatively unsaturated Zn2+ ions in the structure of the Fe-Zn complex are the probable active sites. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: alcoholysis of vegetable oils; Biodiesel; Biolubricants; double-metal cyanides (DMC); esterification of free fatty acids; fatty acid alkyl esters; fatty acid methyl esters; solid Fe-Zn catalysts; transesterification of vegetable oils

Sites for CO2 activation over amine-functionalized mesoporous Ti(Al)-SBA-15 catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2006)
{Activation of CO and its utilization in the synthesis of chloropropene and styrene carbonates over functionalized, mesoporous SBA-15 solids, have been investigated. The surface basicity of SBA-15 was modified with nitrogen-based organic molecules of varying basicity viz., alkyl amines (-NH2), adenine (Ade), imidazole (Im) and guanine (Gua). The surface of SBA-15 was also functionalized with Ti4+ and Al3+ species. The acid-base properties of these modified SBA-15 materials were investigated by temperature-programmed desorption (TPD) and diffuse-reflectance infrared Fourier transform (DRIFT) spectroscopy. NH3 and pyridine were used as probe molecules for acid sites, while CO, was used to characterize the basic sites. CO was activated at the basic amine sites forming surface carbamate species (IR peaks: 1609 and 1446 cm(-1)). The latter reacted further with epoxides adsorbed on the acid sites forming cyclic carbonates. A correlation between the intensity of the IR peak at 1609 cm(-1) and cyclic carbonate yield has been observed. The cyclic carbonate yields were higher when both the acid and base functionalities were present on the surface. The Ti- and Al-SBA-15 functionalized with adenine exhibited the highest catalytic activity and selectivity. There is an optimal dependence (''
Keywords: aromatization; Ga-based zeolites; propane; Si/Al ratio; Si/Ga ratio; zeolitic factors

Syntheses of polycarbonate and polyurethane precursors utilizing CO2 over highly efficient, solid as-synthesized MCM-41 catalyst - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Tetrahedron Letters, 2006)
As-synthesized MCM-41 was used as a reusable, heterogeneous catalyst for the eco-friendly synthesis of cyclic carbonate precursors of polycarbonates via a cycloaddition reaction of CO2 with epoxides. This catalyst is also efficient for the synthesis of alkyl and aryl carbamate precursors of polyurethanes via the reaction of amines, CO2 and alkyl halides. Both these reactions were carried out under mild conditions and without using any solvent or co-catalyst. CO2 is utilized as a raw material replacement for toxic phosgene in the conventional synthesis of these chemicals. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: carbamates; carbon dioxide utilization; CO2 fixation; cyclic carbonates; eco-friendly processes; MCM-41; polycarbonates; polyurethanes

Activation and reactivity of epoxides on solid acid catalysts - Saikia, Lakshi; Satyarthi, J. K.; Srinivas, Darbha; Ratnasamy, P. (Journal of Catalysis, 2007)
The aminolysis of epoxides over novel solid catalysts (Bronsted-acidic SBA-15 functionalized with propylsulfonic acid and Lewis-acidic Ti-MCM-41) is reported. The acidic properties of these catalysts were determined by FTIR spectroscopy and temperature-programmed desorption of pyridine and NH3, respectively. The mesoporous solid acids of the present study are reusable and exhibit significantly higher catalytic activities than known catalysts for opening of the oxirane ring with nitrogen (aromatic and aliphatic amines)-containing and oxygen (alcohols)-containing nucleophiles. A range of beta-amino, alcohols with high regioselectivity and stereoselectivity were synthesized. Adsorption studies as well as the sigmoid shape of the conversion- versus-time plots show that the epoxide and amine compete for adsorption on the acidic sites (-SO3H or Ti4+) on the catalyst surface. Epoxide adsorption and activation on acid sites are the more critical processes. Catalytic activity decreases with increasing basicity of the amines and/or the alcohol, as well as the dielectric constant of the solvent. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aminolysis and alcoholysis of epoxides; beta-Amino alcohols; ring opening of epoxides; SBA-15 functionalized with propylsulfortic acid; Solid acids; Ti-MCM-41

Chemoselective alkane oxidations by reactive superoxovanadium(V) species in vanadosilicate molecular sieves - Srinivas, D.; Ratnasamy, P. (From ZEOLITES to Porous Mof Materials: The 40th Anniversary of International ZEOLITE Conference, Proceedings of The 15th International ZEOLITE Conference, 2007)
Unlike their titanium analogs, vanadosilicate molecular sieves catalyze the oxidation of the terminal (primary) C-H bonds in paraffins. This dissimilarity is attributed to differences in the type of reactive superoxo species generated on contact with oxidant. The latter were identified and characterized by in situ EPR and DRUV-vis spectroscopic techniques. By a suitable choice of silicate structure (VS-1 or V-MCM-41), solvent and oxidant (H(2)O(2), tert.-butyl hydroperoxide or H(2)+O2()), the V-O bond covalency and mode of O-O bond cleavage in the oxo-species and thereby, the chemoselectivity in the oxidation of the terminal carbon atoms in paraffins could be controlled.

Regio- and stereoselective synthesis of beta-amino alcohols over titanosilicate molecular sieves - Satyarthi, Jitendra K.; Saikia, Lakshi; Srinivas, Darbha; Ratnasamy, P. (Applied Catalysis A-General, 2007)
A novel application of titanosilicate molecular sieves in the synthesis of P-amino alcohols via aminolysis of epoxides, at mild and solvent-free conditions, is reported, for the first time. A range of beta-amino alcohols with nearly 100% regio- and stereoselectivity was produced over these reusable solid catalysts in high yields. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Aminolysis of epoxides; synthesis of beta-amino alcohols; Ti-MCM-41; titanosilicate molecular sieves

Spectroscopic and catalytic properties of SBA-15 molecular sieves functionalized with acidic and basic moieties - Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2007)
SBA-15, grafted with Lewis acidic Ti4+ ions and basic amines (imidazole, guanine or adenine) exhibited high catalytic activity in the cycloaddition of CO2 to epoxides yielding selectively cyclic carbonate precursors of polycarbonates. In the second class of materials, the surface of SBA-15 was grafted with thiol or sulfonic acid functionalities. Mn(Salen)Cl was, then, covalently bound to these acidic groups. The resulting catalysts show enhanced chemo-, regio- and stereo-selective catalytic activity in the epoxidation of terpenes such as R-(+)limonene, alpha-pinene and Delta-carene with molecular oxygen. The acid-base properties of these modified SBA- 15 materials were investigated by temperature-programmed desorption and diffuse-reflectance infrared Fourier transform spectroscopy. Ammonia and pyridine were used as probe molecules for acidic sites and CO2 for basic sites. Acidic Ti sites activated epoxides and the grafted basic amines activated CO2. The simultaneous presence of both acidic and basic sites on amine/adenine-functionalized Ti-SBA-15 enabled synergistic enhancement in catalytic activity in the cycloaddition reaction of CO2 to epoxides. When Mn(Salen)Cl was immobilized on thiol or sulfonic acid-functionalized SBA-15, the oxidation state of Mn decreased from +3 to +2. The organo-acidic functional groups (thiol or sulfonic acid) axialk, coordinated to Mn ions modified the electronic structure of Mn ions enhancing the activity and selectivity of Mn(Salen) complexes in aerial oxidation reactions. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aerial oxidation of terpenes; CO2 utilization; cyclic carbonates synthesis; epoxidation; functionalization with acidic and basic moieties; immobilization of Mn complexes; organo-functionalization of SBA-15; solid acid-base catalysts

Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Regiospecific oxyhalogenation of aromatics over SBA-15-supported nanoparticle group IV-VI metal oxides - Saikia, Lakshi; Rajesh, M.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2010)
TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 exhibit efficient catalytic activity for oxyhalogenation of aromatics with the H(2)O(2)-halide ion system. Unlike the hitherto known solid catalysts, these reusable catalysts yield the para-halogenated product with 100% selectivity at 298 K and moderate acidic pH (3-5). The catalytic activity was enhanced by five orders of magnitude when supported on SBA-15.
Keywords: Haloperoxidase activity; Ordered mesoporous silica; Oxyhalogenation of aromatics; SBA-15; Supported metal oxides

Hydrolysis of vegetable oils and fats to fatty acids over solid acid catalysts - Satyarthi, J. K.; Srinivas, D.; Ratnasamy, P. (Applied Catalysis A-General, 2011)
Solid Fe-Zn double-metal cyanide (DMC) complexes exhibit high catalytic activity for hydrolysis of edible and non-edible vegetable oils and animal fat. In a batch reaction, complete conversion of vegetable oil triglycerides to fatty acids with selectivity greater than 73 wt% was obtained at temperatures as low as 463 K, autogenous pressure and with 5 wt% of catalyst. Catalytic activity of DMC was superior to Amberlyst (TM) 70, SAPO-11, H-beta, HY, MoO(x)/Al(2)O(3) and sulfated zirconia. Rates of hydrolysis were greatly enhanced when solvents (tetrahydrofuran or N,N-dimethylformamide), phase transfer agents (tetrapropyl ammonium bromide) and products (a mixture of mono-/diglycerides and fatty acids) or fatty acid was added to the feed. Surface hydrophobicity which enables high wettability and activation of glycerides on active, acidic sites of reusable DMC is attributed to be the major cause for its superior catalytic activity. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Double-metal cyanide complex; Fat splitting; Fatty acids; Hydrolysis of vegetable oils and fats; solid acid catalyst